Scientific foundations of designing specialized agricultural bioengineering complexes - Chernova, I. (Energy and Automation, 2025)
The article considers the design of specialized agricultural bioengineering complexes for biological plant protection based on the use of ontologies. The aim of the study is to develop scientific foundations for the design of specialized agricultural bioengineering complexes. The object of research is specialized agricultural bioengineering complexes. The subject of the research is the use of an ontological approach to the design of intelligent information systems for biological plant protection. Research methods – systemic approach, ontological engineering, free software environment Visual Understanding Environment. An analysis of research by domestic and foreign scientists on the design of specialized agricultural bioengineering complexes was conducted. The processes of designing an intelligent information system for biological plant protection are formalized in the form of ontologies, in particular, structuring actions to manage the production of biological plant protection products (at the technocenosis level), structuring actions to manage the use of biological plant protection products (at the agrotechnocenosis level), and developing a knowledge base of an intelligent information system for biological plant protection. The advantages of using ontologies in designing an intelligent information system for biological plant protection are automation of knowledge analysis, aggregation of knowledge, and increasing the level of competence of a human technologist in the processes of production management and the use of biological plant protection products. Key words: agrotechnocenosis, knowledge base, biological plant protection, intellectual information system, ontologies, technocenosis